2022
DOI: 10.1038/s41398-022-02155-x
|View full text |Cite
|
Sign up to set email alerts
|

Fitness is positively associated with hippocampal formation subfield volumes in schizophrenia: a multiparametric magnetic resonance imaging study

Abstract: Hippocampal formation (HF) volume loss is a well-established finding in schizophrenia, with select subfields, such as the cornu ammonis and dentate gyrus, being particularly vulnerable. These morphologic alterations are related to functional abnormalities and cognitive deficits, which are at the core of the insufficient recovery frequently seen in this illness. To counteract HF volume decline, exercise to improve aerobic fitness is considered as a promising intervention. However, the effects of aerobic fitness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Correspondingly, the different areas of the CA have been shown to be particularly responsive to aerobic fitness changes and aerobic exercise (48,49). At the same time, the CA area is supposed to be specifically prone to volume loss in schizophrenia (29,82).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, the different areas of the CA have been shown to be particularly responsive to aerobic fitness changes and aerobic exercise (48,49). At the same time, the CA area is supposed to be specifically prone to volume loss in schizophrenia (29,82).…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic fitness and exercise are related to increases in the volume of the HF and its subfields, especially in CA3, CA4 and DG, leading to improvements in short-term memory, working memory and general functioning in patients with schizophrenia (44)(45)(46)(47)(48)(49)(50). However, evidence is heterogeneous with comparable examinations contradicting these findings (51)(52)(53)(54)(55).…”
Section: Introductionmentioning
confidence: 99%
“…The volumes of hippocampal subfields were obtained using FreeSurfer software (version 6.0, http://surfer.nmr.mgh.harvard.edu/ , RRID:SCR_001847), which is widely used for healthy adults ( 17 , 48 ) and patients with neuropsychiatric disorder ( 49 , 50 ). FreeSurfer interrogates contrast differences between substructures using previously defined in vivo and ex vivo hippocampal atlases to determine substructure characteristics ( 50 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the utmost investigated brain region is the hippocampus, together with its subfields and the parahippocampal areas. Volumetric studies reported mixed results consequent to aerobic fitness, with evidences for either an increased cortical volume of the hippocampus in schizophrenic patients [25,27,30,35,39] or stable hippocampal grey matter both in clinical high-risk subjects [23,24] and later stages of psychosis [31,36,37]. The same Therefore, the utmost investigated brain region is the hippocampus, together with its subfields and the parahippocampal areas.…”
Section: Exercise Effects On Structural Plasticity In Psychosismentioning
confidence: 99%